Peradaban dan Politik Global Samuel P. Hungtington - Fyan Andinasari Kuen; Hafied Cangara; Hasrullah Hasrullah (Al-MUNZIR, 2022)
AbstractThis paper aims to analyze the birth of new civilizations as a result of global political conflicts with Samuel Huntington's explanation and compare them with the current state of Indonesia. The research method used is critical discourse analysis. Conclusion The review of the book Clash of Civilizations and the Future of World Politics will be explained using critical discourse analysis where in fact some of the predictions written tend to touch several countries in the world, but some don't. For example, Indonesia is able to place itself in global politics dynamically, such as being in a non-aligned and G20 country, and is not touched by friction, clashes or conflicts of shifting civilizations because it has two strong things, namely the nation's motto Bhineka Tunggal Ika and the Pancasila state foundation and many are asked to participate. involved as a peacemaker in horizontal conflicts and humanitarian conflicts in several countries.Keywords: Samuel P. Huntington, Civilization, Global Politics, Indonesian Perspective